Портативный источник излучения радиационного дефектоскопа: полезная модель - Волков В. Г. Владимир Григорьевич; Звонцов А. А. Александр Акимович; Зрелов Ю. Д. Юрий Дмитриевич; Касьянов В. А. Валерий Алексеевич; Рычков М. М. Максим Михайлович; Токач Е. Ф. Евгений Фидельевич; Филимонов А. А. Анатолий Алексеевич; Штейн М. М. Михаил Михайлович
опубл. 20.08.10